THE VARIANCE OF RADIOPAQUE IMAGES COMMONLY FOUND IN PERIAPICAL LESION USING PERIAPICAL RADIOGRAPHIC TECHNIQUE (Review article) - Indra Gunawan; Ria F.; Lusi E, Azhari (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Two pathological views are presented in radiographic imaging: radiolucency and radiopacity. In radiographic examination, radiopaque lesions are reported as the most common manifestation to be found. Opaque lesions are displayed into various depictions thus more specific examination is required to distinguish respective lesions. Objectives: Investigate radiopacity aspect of periapical lesions using literature review to aid dental practitioners obtain final diagnosis, differential diagnosis, and identification of each periapical opaque lesion. Discussion: Assessing respective matter about lucent and opaque lesion images in periapical tissue, this review resulted in the identification of elusive characterization in each opaque lesion. Conclucion: Radiographically, each diagnosis possesses particular characteristic which differ each periapical opaque lesion from another.